Nexus Tools Platform: Web-based comparison of modelling tools for analysis of water-soil-waste nexus. (February 2016) - Mannschatz, T.; Wolf, T.; Hülsmann, S.
Abstract: Exploring the inter-linkages of water, soil and waste resources and advancing an integrated management (or Nexus-) approach requires integrated modelling tools. Numerous models are available dealing with specific environmental processes, covering certain spatial and temporal scales and applying different mathematical process-describing relationships. However, finding and selecting the most appropriate (suite of) model(s) for a particular purpose is challenging, since current inventories do not allow any interactive filtering or model comparison. Therefore, we developed an interactive web-based platform, called Nexus Tools Platform (NTP), for inter-model comparison of existing modelling tools, which provides detailed information and allows for advanced filtering based on real-time visualizations. The alpha version of NTP (September 2015) comprises 73 models and covers a wide range of model types and environmental processes. We present selected NTP application examples for how to find and select the most appropriate modelling tools for a specific application using meta-analysis. Highlights: Analysis of the water-soil-waste nexus requires appropriate modelling tools. A web-based platform for interactive comparison of nexus modelling tools was set up. The need for this platform, its development and implementation is explained. Application examples demonstrate its functionality for selecting appropriate models. An index to evaluate the popularity of modelling tools was developed.